Effect of heat treatment on microstructure and mechanical properties of Ti-5wt-%Ni alloys for use as biomaterial - Cascadan, Daniela [UNESP]; Buzalaf, M. A. R.; Grandini, Carlos Roberto [UNESP] (Taylor & Francis, 2014)
Titanium alloys are among the most important and frequently used class of biomaterials. In addition to biocompatibility, it is important that an implant material present satisfactory mechanical properties that allow long term use in the body. To improve such properties, different heat treatments are used, as well as doping with oxygen. The presence of interstitial oxygen in the crystal lattice causes deformation, increases the hardness, and causes modifications in anelasticity, thereby decreasing the elastic modulus. In this study, an alloy was prepared by arc melting precursor metals, heat and mechanically treated, and doped with oxygen, resulting in samples with different processing conditions. In each condition, the alloy was characterised in terms of amount of oxygen, X-ray diffraction, and optical microscopy. In addition, properties of the alloy, such as hardness and elastic modulus, were analysed.
Keywords: Titanium alloys; Interstitial oxygen; Mechanical properties